Elevação da pressão arterial pulmonar ao esforço físico como marcador de eventos adversos na estenose mitral reumática - Sanny Cristina de Castro Faria (2018)
Aims: Pulmonary hypertension in response to exercise is a marker of hemodynamic severity of the mitral stenosis (MS). However, the factors related to elevated pulmonary pressure with exercise are not well defined. The aim of this study was to assess the parameters associated with a pulmonary pressure response to exercise in patients with pure rheumatic MS. In addition, we aimed to determine the impact of exercise-induced pulmonary hypertension on clinical outcome. Methods and results: One hundred and thirty patients with MS, 94% females, aged 45 ± 11 years underwent exercise echocardiography. A range of echocardiographic parameters were obtained at rest and at peak exercise. A symptom-limited graded ramp bicycle was performed in the supine position. Long-term outcome was a composite endpoint of death or mitral valve intervention either percutaneous or surgical. In the overall population, systolic pulmonary artery pressure (SPAP) increased from 38.3 ± 13.4 mmHg at rest to 65.8 ± 20.7 mmHg during exercise. Increase in mean mitral gradient, right ventricular (RV) function, left atrial (LA) volume, and net atrioventricular compliance (Cn) were independently associated with SPAP at peak exercise, after adjusting for changes in heart rate. During the follow-up period (median of 17 months, range, 1 to 45), 46 adverse clinical events were observed. By multivariable Cox proportional-hazards analysis adjusted for age and gender, SPAP achieved at peak exercise was an important predictor of adverse outcome (adjusted hazard ratio [HR] 1.025; 95% confidence interval [CI] 1.0101.040; p =0.001). NYHA functional class (adjusted HR 2. 459; 95% CI 1.5094.006; p <0.001), and an interaction between valve area and Cn (p =0.001) were also significant predictors of adverse events. Conclusions: In MS patients, the pulmonary artery pressure response to exercise is determined by a combination of factors, including transmitral mean gradient at exercise, Cn, LA volume, and RV function. Pulmonary artery pressure at peak exercise is a strong predictor of clinical outcome, and adds incremental prognostic value beyond that provided by standard resting measurements, including valve area.